2014
DOI: 10.4132/koreanjpathol.2014.48.4.263
|View full text |Cite
|
Sign up to set email alerts
|

The Clinicopathological Significance of Epithelial Mesenchymal Transition Associated Protein Expression in Head and Neck Squamous Cell Carcinoma

Abstract: BackgroundEpithelial mesenchymal transition (EMT) has an important role in invasion and metastasis of tumor cells. The purpose of this study was to evaluate the roles of EMT-associated proteins on progression and metastasis as a prognostic/predictive factor in curatively-resected (R0) head and neck squamous cell carcinoma (HNSCC).MethodsA total of 118 patients who received curative surgery for HNSCC at Inha University Hospital between January 1996 and December 2011 were included. We used protein immunohistoche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 19 publications
(28 reference statements)
5
8
0
Order By: Relevance
“…Our observation is in line with previous immunohistochemistry studies reporting a correlation between EZH2 expression and lymph node metastasis in head and neck cancers . For example, Wang et alshowed a 1.5‐fold increase in EZH2 levels in nodal‐negative as compared to nodal‐positive cancers and Kim et al reported 15% vs 35% EZH2‐positive cancers in subsets of nodal‐negative and nodal‐positive head and neck cancers, respectively. It is believed that EZH2 exerts its oncogenic function through transcriptional deregulation of cancer‐relevant processes including cell differentiation and growth, adhesion, motility, and apoptosis .…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our observation is in line with previous immunohistochemistry studies reporting a correlation between EZH2 expression and lymph node metastasis in head and neck cancers . For example, Wang et alshowed a 1.5‐fold increase in EZH2 levels in nodal‐negative as compared to nodal‐positive cancers and Kim et al reported 15% vs 35% EZH2‐positive cancers in subsets of nodal‐negative and nodal‐positive head and neck cancers, respectively. It is believed that EZH2 exerts its oncogenic function through transcriptional deregulation of cancer‐relevant processes including cell differentiation and growth, adhesion, motility, and apoptosis .…”
Section: Discussionsupporting
confidence: 92%
“…The increasing level of EZH2 expression in patients with higher lymph node metastasis stage suggests a contribution of EZH2 to tumor cell dissemination. In addition, it makes EZH2 an interesting candidate for a clinical biomarker that may aid in decisions on adjuvant treatment in curatively resected HNSCC . Our observation is in line with previous immunohistochemistry studies reporting a correlation between EZH2 expression and lymph node metastasis in head and neck cancers .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations